Anti-MDA5 Antibody-Positive Interstitial Pneumonia with Autoimmune Features Presenting as Amyopathic Hypodermatitic Dermatomyositis: A Case Report - Maria L. Mihailescu (Case Reports in Dermatology, 2021)
Dermatomyositis (DM) and its variant, clinically amyopathic DM, are widely recognized entities. DM sine dermatitis, a variant without skin involvement, is less widely reported. DM with neither muscle nor skin manifestations has not been reported. We herein describe the first account of a patient with a myositis-specific antibody presenting with an array of clinical findings in the absence of both muscle and pathognomonic skin disease. This case report details the multidisciplinary assessment of an anti-melanoma differentiation-associated gene 5 (MDA5) antibody-positive individual with inflammatory polyarthropathy, mucocutaneous capillary changes, and evidence of interstitial lung disease but lacking overt skin and muscle disease. This presentation is paradoxically but appositely deemed to represent a unique form of DM, which may be best described as “amyopathic hypodermatitic dermatomyositis.” Early recognition and documentation of these cases will help to characterize this variant in the future, determine its frequency, and guide management.